Childhood School Performance in Adults Diagnosed with Attention-Deficit/Hyperactivity Disorder. Issue 3 (February 2023) - Vňuková, Martina; Děchtěrenko, Filip; Weissenberger, Simon; Anders, Martin; Ptáček, Radek
Objective: Children with ADHD often tend to underperform in school. This partial study aimed to find out if the school experience of adults with higher ADHD symptomatology differs from those with lower and no ADHD symptomatology. Method: Based on the results of ASRS questionnaires, the respondents were divided into three groups (low, medium, and high) according to the manifested ADHD symptomatology. We explored their school experiences by looking at their grades for behavior at school, notes regarding their attendance, school expulsion, and other school experiences. Results: Children with higher ADHD symptomatology were significantly more likely to be expelled, receive notes for bad behavior, disturbing or forgetting as well as receive reprimands from teachers. Conclusion: Our results show that children with increased ADHD symptomatology experience more difficulties with school behavior, they are frequently reprimanded, and they do receive more negative feedback regarding their attendance and tardiness from teachers.